Investigation of Placenta Tissue Saturation with Glycerol and 1,2-Propane Diol - Bobrova, E. N.; Zinchenko, A. V.; Schetinsky, M. I. (Problems of Cryobiology and Cryomedicine, 2005)
Using differential scanning calorimetry and nuclear magnetic resonance methods we investigated placenta samples’ saturation with glycerol and 1,2-propane diol (1,2-PD). Placenta samples were exposed in 10, 40, 60% (w/w) glycerol and 1,2-PD solutions for 20, 60 min and 24 hrs. It was shown that in placenta tissue there was the formation of 1,2-PD solutions of higher concentrations for all saturating solutions with 1,2-PD in comparison with those with glycerol. A big amount of vitreous phase is formed in placenta for the same equilibration time in 1,2-PD-contained medium.